Determination of Isoflavones in Soybean Flour by Matrix Solid-Phase Dispersion Extraction and Liquid Chromatography with UV-Diode Array Detection - Antonella Aresta; Pietro Cotugno; Federica Massari; Carlo Zambonin (Journal of Food Quality)
A new analytical method, based on liquid chromatography (LC) with UV-diode array detection, for the simultaneous determination of daidzein, genistein, and glycitein and their 7-O-β-D-glucopyranoside (daidzin, genistin, and glycitin, resp.) has been successfully developed. All the calibration curves showed good linearity within the concentration range 0.02–2 μg/ml. The limits of detection and quantitation were 0.057 (genistin and glycitein), 0.124 μg/ml (genistein), 0.190 μg/ml (genistin and glycitein), and 0.410 μg/ml (genistein), respectively. Within-day and between-days precision were found not to be significantly different according to an F-test; values (% RSD) ranged from 2.0 to 2.9%. Extraction and clean-up of soybean flour samples were carried out using matrix solid-phase dispersion extraction (MSPD). The main parameters affecting extraction yield, such as dispersant, type and amount of additives, cosorbent, and extractive solvent, were evaluated and optimized. The average recovery values were between 85.7 and 102.6%. The target isoflavone concentration levels estimated in this work fit existing literature data and were comprised between 39.3 and 345.3 μg/g. The whole procedure has proved to be simple, accurate, precise, and cheap.